Increased mass loss of glaciers in Volcán Domuyo (Argentinian Andes) between 1962 and 2020, revealed by aerial photos and satellite stereo imagery - Falaschi, Daniel; Berthier, Etienne; Belart, Joaquín M. C.; Bravo, Claudio; Castro, Mariano Agustin; Durand, Jorge Marcelo; Villalba, Ricardo (Journal of Glaciology)
We present geodetic mass-balance estimates for ten glaciers (22.6 ± 1.1 km2) around Volcán Domuyo between 1962 and 2020 (and 46 glaciers covering 29 ± 1.5 km2 between 1984 and 2020), derived from airborne, ASTER and Pléiades imagery. Overall, we find a slightly negative mass balance (-0.15 ± 0.09 m w.e. a-1) for the entire 1962-2020 time span. A closer inspection of sub-periods reveals, however, an increasingly negative mass balance with time. The Domuyo glaciers shifted from a moderately positive mass balance of +0.28 ± 0.13 m w.e. a-1 between 1962 and 1984, to a strongly negative mass balance of-0.99 ± 0.19 m w.e. a-1 between 2012 and 2020. An increase in summer temperatures and a decrease in winter precipitation during the last four decades are likely drivers of the observed glacier changes. We support this finding by implementing a minimal glacier model, relying solely on monthly precipitation and air temperatures. The mass-balance evolution detected in Volcán Domuyo is consistent with other sites spread across the Central Andes, suggesting rapidly increasing glacier wastage impacts are occurring at a geographically wider scale. Fil: Falaschi, Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Universidad Nacional de Cuyo. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Departamento de Geografia; Argentina. University of St. Andrews; Reino Unido Fil: Berthier, Etienne. Universite de Toulouse; Francia Fil: Belart, Joaquín M. C. University Of Iceland; Islandia Fil: Bravo, Claudio. Centro de Estudios Científicos; Chile Fil: Castro, Mariano Agustin. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de ...